The Impact of Tax Service Quality and Tax Sanctions on Individual Taxpayer Compliance at the North Bekasi Tax Office (2024) - Natasya Wijaya; Irwansyah Aditya Saputra (Penerbit Hellow Pustaka, 2025)
This research is quantitative with an associative approach. Data were obtained by distributing questionnaires to 100 individual taxpayer respondents registered at the North Bekasi Tax Office. Data analysis techniques used included validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression, t-test, F-test, and coefficient of determination (R²) using IBM SPSS Statistics 20. The results showed that the Tax Sanctions variable did not significantly influence Taxpayer Compliance with a significance value of 0.890 (>0.05). Similarly, the Service Quality variable did not significantly influence Taxpayer Compliance with a significance value of 0.376 (>0.05). Simultaneously, these two variables also had no significant effect on taxpayer compliance, with an F-value of 0.673 (>0.05). The coefficient of determination (R²) of 0.008 indicates that tax sanctions and service quality only explain 0.8% of the variation in taxpayer compliance. Therefore, it can be concluded that tax sanctions and service quality are not dominant factors influencing individual taxpayer compliance at the North Bekasi Pratama Tax Office. Other approaches, such as tax education, moral awareness, and more optimal use of digital technology, are needed to improve tax compliance.